2021
DOI: 10.1021/acsami.1c20720
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput and Controllable Fabrication of Helical Microfibers by Hydrodynamically Focusing Flow

Abstract: Due to the unique spiral geometry, different functional helical fibers are fabricated to perform vital tasks, including cargo transportation, medical treatment, cell manipulation, and so on. Although microfluidic techniques are widely used to fabricate helical fibers, the problems of channel blockage and spinning instability have not been well solved, which limits the mass preparation and practical application of spiral microfibers. In addition, the spinning mechanism is simply limited to liquid rope coiling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…A square membrane with a side length of 10 cm needs helical fiber of at least 10 m long to fully cover the surface, which has a high requirement for the stability of spinning. In our previous study, a new type of microfluidic channel, which was made of stainless steel needles was designed, and the experimental results showed that this new design was more stable and clogged less frequently than the conventional microchannels, which were made of tapered glass capillaries 27 . Even with nanoparticles loaded in the internal phase, a helical microfiber of nearly 100 m was still successfully generated.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A square membrane with a side length of 10 cm needs helical fiber of at least 10 m long to fully cover the surface, which has a high requirement for the stability of spinning. In our previous study, a new type of microfluidic channel, which was made of stainless steel needles was designed, and the experimental results showed that this new design was more stable and clogged less frequently than the conventional microchannels, which were made of tapered glass capillaries 27 . Even with nanoparticles loaded in the internal phase, a helical microfiber of nearly 100 m was still successfully generated.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, a new type of microfluidic channel, which was made of stainless steel needles was designed, and the experimental results showed that this new design was more stable and clogged less frequently than the conventional microchannels, which were made of tapered glass capillaries. 27 Even with nanoparticles loaded in the internal phase, a helical microfiber of nearly 100 m was still successfully generated. Therefore, here we choose this new type of channel for the preparation of spiral fibers.…”
Section: Microfluidic Preparation Of Calcium Alginate Helical Microfi...mentioning
confidence: 99%
See 3 more Smart Citations